Upaya Meningkatkan Pemahaman Konsep Bilangan melalui Media Kartu Angka untuk Pengembangan Kognitif - Rosanna Rangkuti; Rabitah Hanum Hasibuan (Aṭfāluna: Journal of Islamic Early Childhood Education, 2018)
This research was conducted due to low understanding of children's concept in TK Haholongan. The purpose of this research is to know the increasing understanding of number concept through number of card and to know the constraints faced and how to overcome it in increasing understanding of number concept through number card executed in TK. Haholongan Padangsidimpuan. The research conducted is a class action study consisting of 2 observations consisting of 4 stages, namely planning, implementation, observation, and reflection. The subject of this study was group B of TK Haholongan Padangsidimpuan. Before action is done, the level of understanding of the child concept is still very low, after the action on the cycle I done then obtained the success rate of the implementation of a number concept understanding through the card media of 33% and in cycle II Increased to 74%. After research is conducted from the pre-cycle, cycle I, and cycle II then it can be concluded that understanding the concept of numbers through the card media numbers for the cognitive development of children can increase.